'Period doubling' induced by optimal control in a behavioral SIR epidemic model. (August 2022) - Sharbayta, Sileshi Sintayehu; Buonomo, Bruno; d'Onofrio, Alberto; Abdi, Tadesse
Abstract: We consider a behavioral SIR epidemic model to describe the action of the public health system aimed at enhancing the social distancing during an epidemic outbreak. An optimal control problem is proposed where the control acts in a specific way on the contact rate. We show that the optimal control of social distancing is able to generate a period doubling–like phenomenon. Namely, the 'period' of the prevalence is the double of the 'period' of the control, and an alternation of small and large peaks of disease prevalence can be observed. Highlights: Behavioral epidemiology SIR model Enhancing the social distancing Optimal control of social distancing Period doubling–like phenomenon Alternation of small and large peaks of disease prevalence is observed.